2,3-Dibromo-1-(4-methylphenyl)-3-(5-nitrofuran-2-yl)propan-1-one - Fun, Hoong-Kun (International Union of Crystallography, 2010)
In the title compound, C(14)H(11)Br(2)NO(4), the whole molecule is disordered over two positions with a refined occupancy ratio of 0.539 (9):0.461 (9). The 2-nitrofuran and toluene groups are approximately planar, with maximum deviations of 0.176 (11) and 0.121 (14) Å, respectively, in the major component and 0.208 (11) and 0.30 (17) Å in the minor component. The dihedral angles between the 2-nitrofuran and toluene groups are 8.7 (5) and 8.0 (9)° for the major and minor components, respectively. In the crystal, weak intermolecular C—H⋯O interactions connect molecules into a three-dimensional network, generating R (2) (1)(6) ring motifs.